Study guide for drug therapy in nursing - Aschenbrenner, Diane S.; Venable, Samantha J. (Lippincott Williams & Wilkins, 2012)
A study companion to "Drug Therapy in Nursing, Fourth Edition" textbook. It helps students to build essential knowledge and develop practice skills. It includes Top Ten Things to Know to prioritize essentials of nursing drug therapy and NCLEX questions for every chapter.